Epidemiological profile and outcome of pediatric poisoning: a prospective observational study from a tertiary care center - Reddy, A. Bhaskar; Reddy, K. Venkataramana; Soren, C.; Eluzai, Zion; Srikanth, M. (International Journal of Contemporary Pediatrics, 2018)
Background: Acute poisoning in children is one of the common causes for emergency hospital visit in developing countries. Objectives of the present research was aimed to study the magnitude, nature, age, sex, socioeconomic status and outcome of poisoning in children aged <15 years. Methods: This prospective study was conducted for a period of 1 year between January 2017 to December 2017, at S.V.S. Medical College and Hospital, Mahabubnagar, Telangana. All poisoning cases under the age of 15 years were included in this study. Results: Out of 1975 admitted patients, 98 (5%) cases were due to acute poisoning, 52 (53.1%) were males and 46 (46.9%) were females. The majority of the poisoning was accidental (78, 79.6%) in nature and found to be common in the age group of 0-5 years (69, 70.4%). Majority of children belonged to upper lower (35, 44.9%) and lower (20, 25.6%) socio-economic status. Kerosene (40, 40.8%) was the most common poisoning agent, followed by household compounds (22, 22.4%). 82 (83.7%) children had complete recovery, whereas 5 (5.5%) children died, all due to late visit to the hospital. Conclusions: Kerosene is the most common agent in paediatric poisoning in children, followed by household compounds. It is common in 0-5 years of age group and mostly accidental in nature. Corrosives were the common agent involved in suicidal poisoning.